Reflections on the role of consultant radiographers in the UK: What is a consultant radiographer?. Issue 1 (February 2016) - Booth, L.; Henwood, S.; Miller, P.
Abstract: Context: This paper is the second paper from a two year in depth case study, exploring the role of consultant radiographers in the UK. Methods: A longitudinal case study approach was used to determine the role of consultant radiographers. Interviews were used to explore experiences of being a consultant, which were analysed using thematic analysis. Eight consultant radiographers participated (Note, two of the consultants withdrew after the first interview due to workload). Therefore two consultants were interviewed only once. The remaining six consultants were interviewed twice over a 12 month period. Findings: The data presented in this paper explores the nature of the role, differences between roles, the four domains of practice, and how the role fits into local organisational structures. The study shows wide variation in the types of roles undertaken, reflecting that the creation of these roles were in response to local clinical need and often related to an individual practitioner's skills. The broad scope of the role was shown across all the consultants, with evidence of roles developing into new areas of service delivery. Conclusions: The paper offers insight into the role(s) of consultant radiographers in the UK. The range and scope of their practice is extensive, with much variation. It is evident that the clinical aspect of the role dominates, with research being the least supported domain of practice. There remains a lack of clarity around the role, with concerns about remuneration and other limitations that may restrict the role developing further. Highlights: This paper shows the variation in roles between consultant radiographers. The commonality with medical roles is highlighted. Problem solving is identified as a core skill in consultant radiography. Consultants offered evidence of the roles developing service provision. While all four domains of practice are covered, research is the least well supported.